Talk with you like a woman : African American women, justice, and reform in New York, 1890-1935 - Hicks, Cheryl D., 1971- (Gender & American culture., 2010)
With this book, Cheryl Hicks brings to light the voices and viewpoints of black working-class women, especially southern migrants, who were the subjects of urban and penal reform in early twentieth-century New York. In need of support as they navigated the discriminatory labor and housing markets and contended with poverty, maternity, and domestic violence, black women instead found themselves subject to hostility from black leaders, urban reformers, and the police. Through their actions as well as their words, black working-class women challenged prevailing views regarding black women and mor.